Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/wer.1166
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of organic and inorganic pollutants in groundwater

Abstract: Depletion of groundwater resources and continued decline in overall groundwater quality is a cause of concern because large human population around the world uses groundwater as a source of drinking water. This paper presents a comprehensive review of studies published in the year 2018 that documented issues of groundwater pollution, sources, and distribution reported from across the world due to anthropogenic, hydroclimatogical, and natural processes. Groundwater pollution due to organic contaminants focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…As consequence, metal-induced inhibition of GSTs interferes with intracellular detoxification of organic xenobiotics or endobiotic metabolites which may lead to unpredictable toxicological consequences for organisms. This fact is of particular importance as under ecological conditions organic contaminants are often found together with metal contaminants [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As consequence, metal-induced inhibition of GSTs interferes with intracellular detoxification of organic xenobiotics or endobiotic metabolites which may lead to unpredictable toxicological consequences for organisms. This fact is of particular importance as under ecological conditions organic contaminants are often found together with metal contaminants [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Bromide may interfere with thyroid homeostasis, particularly competing with I uptake and I clearance [119,120] however, human toxicity data demonstrated that polybrominated compounds may interfere with gonadal function and sexual steroids' metabolism [118]. Fluoride and fluorinated compounds has been found in different rock-forming minerals, fertilizers, pesticides, and propellants, and has also been found in drinking water generally at acceptable levels according to regulatory agencies (<1.5 mg/L or <4 mg/L) [121] and groundwater [122]. Considering that a low dose of fluoride increases overall oral health, several countries add it to their public water supply at 0.7 to 1.5 mg/L [118].…”
Section: Overview On Other Halogenate Compoundsmentioning
confidence: 99%
“…O tipo de mecanismo e o desempenho das técnicas de remediação térmica dependem diretamente das características dos contaminantes, que podem ser orgânicos ou inorgânicos. Dentre os contaminantes orgânicos estão os combustíveis, solventes, tintas, colas e adesivos, produtos farmacêuticos, compostos perfluorados (presentes em retardantes de chama), pesticidas e herbicidas (WANG et al 2013, KURWADKAR 2019. Os contaminantes orgânicos podem ser classificados em compostos orgânicos voláteis (COV ou VOC, do inglês Volatile Organic Compounds) e semivoláteis (SVOC -Semi-Volatile Organic Compounds).…”
Section: Mecanismos De Remoção Dos Contaminantes Pela Temperaturaunclassified